PENGARUH PERSEPSI KEMUDAHAAN TERHADAP NIAT BERKELANJUTAN DI MEDIASI OLEH KEPERCAYAAN - Dafiq Ilham Akbar; Agung Yuniarinto (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
This study was conducted on the users of Netflix, a video-on-demand streaming service provider, in Malang city. The independent variable is perceived ease of use (X), while the mediating variable is trust (Z), and the dependent variable is continuance intention (Y). The objective of this research is to identify and analyze the effect of perceived ease of use on continuance intention with the mediation of trust. Since this study aims to explain the relationship between or the effect of variables being studied, this research is categorized as causal research. The respondents of this research are 130 users of Netflix in Malang city. The data was harvested from the respondents through Likert scaled questionnaires and was analyzed using path analysis to identify the direct and indirect effects. The research instruments were assessed using validity and reliability tests performed in SPSS 25. This study finds that perceived ease of use directly has a positive and significant effect on continuance intention and the trust of the users. Furthermore, trust positively and significantly affects continuance intention and is able to mediate the effect of perceived ease of use on continuance intention.